A Cryptogenic Stroke Associated With Infective Endocarditis and Antiphospholipid Antibody Syndrome: Case Report and Literature Review - Chen, Lei; Zhang, Ping; Zhu, Xuan; Zhang, Minmin; Deng, Benqiang (Frontiers in Neurology, 2022)
Introduction: Accurate definition of stroke etiology is crucial, as this will guide effective targets for treatment. Both antiphospholipid antibody syndrome (APS) and infective endocarditis (IE) can be independent risk factors for ischemic stroke in young adults. When an embolic stroke occurs with IE and APS simultaneously, the origin of the embolic source is difficult to identify. Case Report: A 19-year-old man was admitted to the hospital for the onset of stroke. A diagnosis of APS was made accompanied by IE after a series of examinations. We identified aortic valve vegetation as the embolic source. Although both APS and IE can induce valve vegetation, we considered IE to be the primary cause according to the infective clues. Despite treatment with ampicillin, the patient’s fever persisted, and surgical aortic valve replacement was performed urgently. The patient recovered without recurrence of stroke during the one-year follow-up. Conclusion: A considerable challenge for physicians is evaluating all the signs suggestive of embolic sources in acute stroke and identifying the primary etiology when there are multiple causes. Early diagnosis and surgical intervention for bicuspid aortic valve vegetation complicated by acute stroke may yield favorable clinical results.